Implementation of a Multicultural Approach in the Evaluation of Educational Programs at MAN 2 Pamekasan School - Maura Aulia Mardatila; Rusdiana Navlia (Penerbit Hellow Pustaka, 2025)
This study aims to describe the application of a multicultural approach in evaluating educational programs at MAN 2 Pamekasan in order to create a fair, inclusive, and socially just education system. This approach is important because students come from various social, economic, and cultural backgrounds, so that objective assessments and respect for differences are needed. The research method used descriptive qualitative with observation, interviews, and documentation. The results show that multicultural values ​​are integrated in learning and evaluation through adaptive and contextual strategies that foster attitudes of tolerance, empathy, and solidarity. Teachers apply James A. Banks' models such as the Contribution Approach and Additive Approach. Supporting factors include the vision of a madrasah that is moral and globally competitive, teacher professionalism, and the local culture of bhuppa'-bhabbhu'-ghuru-rato. The obstacles include limited teacher understanding and suboptimal supporting facilities. Overall, the multicultural approach contributes positively to improving the quality of learning and the formation of tolerant characters in the madrasah environment.